KONSTRUKSI MAKNA TUHAN MELALUI KARTUN DALAM KUIS ONLINE (Analisis Semiotika Kartun Kuis “Ketika Tuhan Menciptakan Saya” Yang Terdapat Pada Situs Web Vonvon Indonesia) - Wa Ode Seprina (Universitas Bunda Mulia, 2015)
Variety entertaining online quiz that is now easy to find and connect directly with social networking sites. Some of them often use cartoon as dayak appeal, but some cartoon character turns itidak presented in accordance with the values held by a society, which then affects how the cartoons were produced. Cartoons be a reflection of reality, where reality is undergoing a process of reproduction, which produces seuatu forms of representation depicted in the cartoon. The events described by the cartoons usually contain elements of humor or satire, such events are often not really happen. However, the form of representation contained in cartoons still take reality as the source. He is a reflection of the realities that exist in society. In the process of producing a cartoon, cartoonist produces a form of representation of reality. A form of representation that can not escape the influence of interests that arise from the media, the public, and of the cartoonists themselves. Order thinking is, therefore, lead to forms of representation that exist in the cartoon has a particular ideology. This opens up a space for researchers to construct ideologically owned by cartoons, through semiotics as a method in social research. In this study, researchers looked at how the representation of God in South Korean online media to view the position of God in society. Therefore, in interpreting signs in cartoons, researchers used a semiotic approach Barthes. Keywords: Cartoon, Semiotic, Representation of God